Isolated intramuscular cysticercosis : a rare condition and a diagnostic challenge - Gupta, Saransh; Gupta, Srishti; Kalra, Mukesh; Khan, Inam Danish (Bangladesh Journal of Medical Science, 2017)
Cysticercosis is an infection of pork tapeworm, Taenia Solium. It is difficult to diagnose an isolated intramuscular cysticercosis due to vague clinical symptoms. We report a case of 30 year old male presenting with a vague lump on the left shoulder. On imaging it was found out to be a case of isolated intramuscular cysticercosis. The diagnosis was further confirmed on fine needle aspiration and histopathology examination. This case report highlights the importance of considering cysticercosis as a differential to soft tissue swellings apart from being a rare entity. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.170-173